Electroconductive Gelatin/Alginate/ Graphene Hydrogel Based Scaffold for Neural Tissue Repair - Pegah Madaninasab; Mahshid Mohammadi; Sheyda Labbaf (Macromolecular Materials and Engineering)
Abstract A composite polymeric scaffold of gelatin/alginate /graphene is fabricated through freeze‐drying technique. Initially, a hydrogel system comprised of gelatin/alginate (1:1) is prepared, and then the effect of different amounts of graphene carboxyl nanosheets (1,1.5, 2, and 2.5 wt.%) on the resultant structural properties are thoroughly evaluated. The swelling ratio, biodegradability, electrical and mechanical properties of bio‐composite hydrogels are controlled by manipulating the concentration of graphene‐COOH. The significant increase in the electrical conductivity is observed with the addition of 2.5% graphene‐COOH, and the electrical conductivity increased from 8.525 × 10−7 ± 0.01 S cm−1 to 7.644 × 10−4 ± 0.04 S cm−1. Also, the biocomposite hydrogels exhibited compressive and tensile strength ranging from 25 to 382 KPa and 11.4 to 148 KPa with an increase in the concentration of graphene‐COOH. The simplicity, low cost, tunable mechanical properties, and optimal electrical conductivity of the hydrogel system presented in this study highlight its potential as nerve tissue replacement.